2016
DOI: 10.1007/s00216-016-9585-x
|View full text |Cite
|
Sign up to set email alerts
|

VHH antibodies: emerging reagents for the analysis of environmental chemicals

Abstract: A VHH antibody (or nanobody) is the antigen binding fragment of heavy chain only antibodies. Discovered nearly 25 years ago, they have been investigated for their use in clinical therapeutics and immunodiagnostics, and more recently for environmental monitoring applications. A new and valuable immunoreagent for the analysis of small molecular weight environmental chemicals, VHH will overcome many pitfalls encountered with conventional reagents. In the work so far, VHH antibodies often perform comparably to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 80 publications
0
83
0
Order By: Relevance
“…These types of homodimeric, light chain-less antibodies have evolved through convergent evolution (Brooks et al, 2018), in at least two groups (camelids and cartilaginous fish), and their variable binding domains (V H H S ) are of great value for therapeutic and diagnostic applications (Muyldermans, 2013;Criscitiello, 2014;Steeland et al, 2016;Könning et al, 2017;Henry et al, 2019). Nanobodies can act against challenging targets such as small molecules and toxins (Wesolowski et al, 2009;Bever et al, 2016), viruses (Wei et al, 2011;Hassiki et al, 2016;Vanlandschoot et al, 2011;Cohen, 2018), enzymes (Muyldermans, 2013), ion channels (Wei et al, 2011;Danquah et al, 2016) and G protein-coupled receptors GPCRs (Cromie et al, 2015). Llama nanobodies have been shown to tether to early endosomes and to mitochondria (Traub, 2019), be used for diagnostics (Shriver-Lake et al, 2018), be used for design of cancer immunotherapeutics (Hussack et al, 2018;Bannas and Koch-Nolte, 2018;Rossotti et al, 2019) and have been approved for passive immunotherapy (Sheridan, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These types of homodimeric, light chain-less antibodies have evolved through convergent evolution (Brooks et al, 2018), in at least two groups (camelids and cartilaginous fish), and their variable binding domains (V H H S ) are of great value for therapeutic and diagnostic applications (Muyldermans, 2013;Criscitiello, 2014;Steeland et al, 2016;Könning et al, 2017;Henry et al, 2019). Nanobodies can act against challenging targets such as small molecules and toxins (Wesolowski et al, 2009;Bever et al, 2016), viruses (Wei et al, 2011;Hassiki et al, 2016;Vanlandschoot et al, 2011;Cohen, 2018), enzymes (Muyldermans, 2013), ion channels (Wei et al, 2011;Danquah et al, 2016) and G protein-coupled receptors GPCRs (Cromie et al, 2015). Llama nanobodies have been shown to tether to early endosomes and to mitochondria (Traub, 2019), be used for diagnostics (Shriver-Lake et al, 2018), be used for design of cancer immunotherapeutics (Hussack et al, 2018;Bannas and Koch-Nolte, 2018;Rossotti et al, 2019) and have been approved for passive immunotherapy (Sheridan, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This limited sample represents an interesting mix of ligand-dependent and -independent modes-of-action for the blocking of RON signaling. Many examples document the ability of the outbred camelid’s immune response to generate nanobodies against challenging targets including ion channels (2931), GPCRs (32, 33), small molecules and toxins (34, 35), viruses (34, 36) and enzymes (2). To our knowledge, this is the first example to illustrate the potential extent of an outbred camelid’s functional immune response in terms of sequence diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported the isolation of hapten-specific V H Hs without investigating their structures, 119 although several also reported weaker and inconsistent serum heavy chain-only IgG titers compared with conventional IgG titers against the hapten. No studies have reported hapten-specific V NAR s, and only one study has described a carbohydrate-specific V H H directed against Neisseira meningitidis lipopolysaccharide; 120 at least two camelid V H Hs have been described that bind to glycopeptide epitopes.…”
Section: Single-domain Antibodies Directed Against Small Moleculesmentioning
confidence: 99%